Immunological imprint of COVID‐19 on human peripheral blood leukocyte populations. Issue 3 (22nd November 2020) - Kratzer, Bernhard; Trapin, Doris; Ettel, Paul; Körmöczi, Ulrike; Rottal, Arno; Tuppy, Friedrich; Feichter, Melanie; Gattinger, Pia; Borochova, Kristina; Dorofeeva, Yulia; Tulaeva, Inna; Weber, Milena; et al.
Abstract: Background: SARS‐CoV‐2 has triggered a pandemic that is now claiming many lives. Several studies have investigated cellular immune responses in COVID‐19‐infected patients during disease but little is known regarding a possible protracted impact of COVID‐19 on the adaptive and innate immune system in COVID‐19 convalescent patients. Methods: We used multiparametric flow cytometry to analyze whole peripheral blood samples and determined SARS‐CoV‐2‐specific antibody levels against the S‐protein, its RBD‐subunit, and viral nucleocapsid in a cohort of COVID‐19 convalescent patients who had mild disease ~10 weeks after infection (n = 109) and healthy control subjects (n = 98). Furthermore, we correlated immunological changes with clinical and demographic parameters. Results: Even ten weeks after disease COVID‐19 convalescent patients had fewer neutrophils, while their cytotoxic CD8 + T cells were activated, reflected as higher HLA‐DR and CD38 expression. Multiparametric regression analyses showed that in COVID‐19‐infected patients both CD3 + CD4 + and CD3 + CD8 + effector memory cells were higher, while CD25 + Foxp3 + T regulatory cells were lower. In addition, both transitional B cell and plasmablast levels were significantly elevated in COVID‐19‐infected patients. Fever (duration, level) correlated with numbers of central memory CD4 + T cells and anti‐S and anti‐RBD, but not anti‐NC antibody levels. Moreover, a "young immunological age" as determined by numbers of CD3 + CD45RA + CD62L + CD31 + recent thymic emigrants was associated with a loss of sense of taste and/or smell. Conclusion: Acute SARS‐CoV‐2 infection leaves protracted beneficial (ie, activation of T cells) and potentially harmful (ie, reduction of neutrophils) imprints in the cellular immune system in addition to induction of specific antibody responses. Abstract : Ten weeks after disease, COVID‐19 patients had fewer neutrophils compared to subjects without COVID‐19, while their cytotoxic CD8 + T cells were still activated. In COVID‐19 patients both CD3 + CD4 + and CD3 + CD8 + effector memory cells, transitional B cells and plasmablast levels were higher, while CD25 + Foxp3 + T regulatory cells were lower than in subjects without COVID‐19. Fever duration correlated with higher numbers of central memory CD4 + T cells, anti‐S and anti‐RBD antibody levels, while loss of taste/smell was associated with higher levels of recent thymic emigrants. Abbreviations: COVID‐19, coronavirus disease 2019; ELISA, enzyme‐linked immunosorbent assay; KRECs, kappa‐deleting recombination excision circles; qPCR, quantitative PCR; RBD, receptor‐binding domain of SARS‐CoV2 spike protein; TRECs, T‐cell receptor excision circles; S, spike protein of SARS‐Cov2; SARS‐CoV‐2, severe acute respiratory syndrome coronavirus 2.